SENSIBLE DIAGNOSES FOR SENSIBLE CLINICIANS: THE NEW EDITION OF THE PSYCHODYNAMIC DIAGNOSTIC MANUAL (PDM-2) - Vittorio LINGIARDI, Nancy MCWILLIAMS (Main Issues Of Pedagogy And Psychology, 2021)
The article analyzes psychodynamic clinical models focused on clinical case formulation and treatment planning, offers practitioners empirically grounded and clinically validated alternatives to such personality maps as the Diagnostic and Statistical Manual of Mental Disorders (DSM) and the International Classification of Diseases (ICD). The PDM-2 diagnostic model aims to provide a systematic description of healthy functioning and personality disorders; individual profiles of mental functioning (including patterns of relationships with other people, understanding and expressing feelings, overcoming stress and anxiety, regulating impulses, observing one's own emotions and behavior and forming moral judgments, etc.); as well as symptom patterns, including differences in each person's subjective experience of symptoms and in the subjective experiences of treating therapists.